PERCEPÇÃO DOS LOJISTAS DO CAMELÓDROMO DE CAXIAS DO SUL SOBRE O REGIME DE TRIBUTAÇÃO UNIFICADA - Paola Eliza Bacarin Rebolledo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
The Brazilian informal work Brazilian, mainly represented by “sacoleiro” and “camelô”, is sustained, in most cases, by the sales of products brought in a clandestine way from Paraguay. Receita Federal of Brazil attacks this illegal import daily. In order to combat this kind of commerce in a more effective way the United Tribute Regime was created, it allows the import of goods from Paraguay, through the payment of taxes and federal contributions. Before this new law, the “camelô” has the possibility of selling goods of legal origin, without suffering the feared seizures. Therefore, a search was done in two phases, the first one qualitative and the second one quantitative. In the first phase, interviews were conducted with the president of Associação dos Camelôs of Caxias do Sul and with a tax auditor of Delegacia da Receita Federal do Brasil em Caxias do Sul. In the second phase, a questionnaire was applied to the shopkeepers of the “camelódromo” of Caxias do Sul. Overall, the results showed that the law is seen as beneficial, but only a few know it, and this is the main reason for the poor adherence of the “camelódromo” in Caxias do Sul.